Patau syndrome - a case report - Bishwajeet Saikia; Bipul Kumar Das; Amitav Sarma (National Journal of Clinical Anatomy, 2014)
Patau syndrome is a rare and one of the most severe forms of autosomal trisomies. Having a karyotype of trisomy 13, it is associated with high rate of pregnancy loss and poor infant survival rate. The incidence is 1 in 20,000 live births. The common features associated with Patau syndrome are mental retardation, congenital heart defects, cleft lip and palate, eye defects, Polydactyly, scalp defects and holoprosencephaly. We report a newborn with most of the clinical features consistent with Patau syndrome. Fluorescence in situ hybridization (FISH) technique was used to determine the karyotype and confirm the diagnosis.